A novel cyclic peptide (Naturido) modulates glia-neuron interactions in vitro and reverses ageing-related deficits in senescence-accelerated mice. - Shinichi Ishiguro; Tetsuro Shinada; Zhou Wu; Mayumi Karimazawa; Michimasa Uchidate; Eiji Nishimura; Yoko Yasuno; Makiko Ebata; Piyamas Sillapakong; Hiromi Ishiguro; Nobuyoshi Ebata; Junjun Ni; et al. (PLoS ONE)
The use of agents that target both glia and neurons may represent a new strategy for the treatment of ageing disorders. Here, we confirmed the presence of the novel cyclic peptide Naturido that originates from a medicinal fungus (Isaria japonica) grown on domestic silkworm (Bombyx mori). We found that Naturido significantly enhanced astrocyte proliferation and activated the single copy gene encoding the neuropeptide VGF and the neuron-derived NGF gene. The addition of the peptide to the culture medium of primary hippocampal neurons increased dendrite length, dendrite number and axon length. Furthermore, the addition of the peptide to primary microglial cultures shifted CGA-activated microglia towards anti-inflammatory and neuroprotective phenotypes. These findings of in vitro glia-neuron interactions led us to evaluate the effects of oral administration of the peptide on brain function and hair ageing in senescence-accelerated mice (SAMP8). In vivo analyses revealed that spatial learning ability and hair quality were improved in Naturido-treated mice compared with untreated mice, to the same level observed in the normal ageing control (SAMR1). These data suggest that Naturido may be a promising glia-neuron modulator for the treatment of not only senescence, but also Alzheimer's disease and other neurodegenerative diseases.